Does the performance assessment of students during surgery clerkship in a medical faculty jeopardize the objectivity of unbiased structured clinical examination? - Daldal, Emin; Dagmura, Hasan; Bakir, Huseyin; Dasiran, Fatih; Ihsan Saglam, Ali; Demir, Osman; Yidirim, Murat; Okan, Ismail; Bulbuloglu, Ertan (Annals of Medical Research, 2021)
Aim: Objective structured clinical examination (OSCE) has become an important assessment method in medicine which is more reliable than traditional exams. Faculty members make an opinion about the students during their clerkship. We aimed to investigate whether their judgments affect the scoring in the OSCE application.Material and Methods: The study was planned prospectively. 4th-year students participating in the OSCE was identified as the working group. At the end of the clerkship, the faculty members gave a performance assessment (PA) score including the professional attitude of the students. PA and OSCE scores were compared. Two other faculty members participated all OSCE stations as external evaluators.Results: There was a difference between OSCE and PA scores. Fewer students were successful at OSCE than PA (p=0.002). While the mean PA scores of three of the five faculty members were statistically similar, other two were different. The scores given by the responsible faculty members and the external evaluators from the faculty of internal medicine were similar (p>0.05). The evaluators from the surgical faculty gave lower scores statistically different from both groups (p0.05). There was a strong relationship between the scores given by the faculty members responsible for the OSCE application and the faculty members from the surgical faculty (r=0.936; p0.001) and those from the internal medicine faculty (r=0.947; p0.001).Conclusion: PA scores of the faculty members did not affect the OSCE scores which were supported by the external observers. The OSCE assessment was not influenced by the PA, and was found to be reliable.
Keywords: Objective structured clinical examination; performance score; professionalism; reliability